Alteration of the microRNA expression profile during the activation of pancreatic stellate cells. (March 2014) - Masamune, Atsushi; Nakano, Eriko; Hamada, Shin; Takikawa, Tetsuya; Yoshida, Naoki; Shimosegawa, Tooru
Abstract Objective. Pancreatic stellate cells (PSCs) play a pivotal role in the pancreatic fibrosis associated with chronic pancreatitis and pancreatic cancer. In response to pancreatic injury or inflammation, PSCs are activated to myofibroblast-like cells. MicroRNA (miRNA) is a small RNA, consisting of 17–25 nucleotides, which targets 3'-untranslated region sequences of mRNA. miRNAs regulate a variety of cell functions such as cell proliferation, differentiation, and carcinogenesis. We examined here whether the miRNA expression profiles are altered during the activation of PSCs. Materials and methods. Rat PSCs were isolated from the pancreas tissue of male Wistar rats. PSCs were activated in vitro by culture in serum-containing medium. miRNAs were prepared from quiescent (day 1) PSCs and culture-activated (day 14) PSCs. Agilent's miRNA microarray containing probes for 680 miRNAs was used to identify differentially expressed miRNAs. Ingenuity Pathway Analysis (IPA) was used for the integrated analysis of altered miRNAs. Results. Upon activation, 42 miRNAs were upregulated (>2.0-fold) and 42 miRNAs were downregulated (<0.5-fold). Upregulated miRNAs included miR-31, miR-143, and miR-221. Downregulated miRNAs included miR-126, miR-146a, and miR-150. IPA revealed the most impacted biological processes including cellular development, cellular growth, and cell movement. Interestingly, IPA identified 22 miRNAs affected both in pancreatic cancer and PSC activation. The top network generated by IPA revealed the interactions of altered miRNAs with signaling pathways such as p38 mitogen-activated protein kinase, extracellular-signal–regulated kinase, and Smad2/3. Conclusions. Our results suggest a novel role of miRNAs in the activation of PSCs.